Synthesis of Naproxen Esters and Evaluation of their In vivo and In silico Analgesic and Anti-inflammatory Activities - Akter, Mansura; Mahmud, Zobaer Al; Nasir Uddin, Mir Muhammad; Das, Raju; Rahman, S M Abdur (Dhaka University Journal of Pharmaceutical Sciences, 2023)
Three consecutive alkyl esters methyl (1), ethyl (2) and isopropyl (3) esters were synthesized from naproxen by direct Fischer esterification reaction and were evaluated for their in vivo and in silico analgesic and antiinflammatory activities. Methyl and ethyl ester showed potent peripheral analgesia with 82.09% and 82.59% writhing inhibition, respectively compared to that of naproxen (64.68% inhibition) at equivalent dose of 25 mg/kg bw. In antiinflammatory study, all the three esters generated 96.75%, 91.54% and 90.65% inhibition of inflammation at 5th hour, similar to that obtained by naproxen (95.12% inhibition). Molecular docking study suggested that methyl ester had the highest binding energy towards COX-2 enzyme, while isopropyl ester possessed the lowest energy, and also exhibited the lower Vander Waals interaction that might affect COX inhibition. Moreover, all the compounds had satisfactory ADME profile. Again, methyl ester satisfied the safety issues, while other compounds might have cardio toxicity. Dhaka Univ. J. Pharm. Sci. 22(1): 105-114, 2023 (June)